Network Externalities and Downstream Collusion under Asymmetric Costs: A Note - Jen-Yao Lee; Chen-Chia Fan; Chien-Shu Tsai (Games, 2023)
This paper considers the collusive stability of downstream competition in a vertical market with network externalities and cost asymmetry. A dynamic collusion game is constructed, and backward induction is employed to solve the subgame perfect Nash equilibrium. We show that larger network externalities lead to less collusive incentive for an inefficient firm, while for an efficient firm, this depends on the efficiency gap. An increase in network externalities will destabilize the downstream collusion when the cost asymmetry is large and network externalities are relatively weak.